THE SOCIAL CONTEXT OF KENTISH RAISING: ISSUES IN OLD ENGLISH SOCIOLINGUISTICS - Trousdale, Graeme (International Journal of English Studies, 2009)
This article considers issues in Old English sociolinguistics, in relation to specific changes affecting the low front vowels in ninth-century Kentish, as manifest in spelling variation in charters of the time. This change is referred to as Kentish Raising (Hogg 1988). It is suggested that variationist sociolinguistics is not an appropriate framework within which to explain Kentish Raising, since the nature of the data is such that a variationist approach is untenable. A reconstruction of the social, political and cultural situation in ninth-century Kent is provided, which examines Mercian influence in the period, and suggests that a Mercian-driven change from above (Second Fronting) cannot be the source of Kentish Raising. Finally, it is proposed that recent work in genetic anthropology, which seeks to discover more about the nature and extent of the continental migrations, may be useful in understanding the social context in which the varieties of Old English existed and developed.